Composites based on MIL-100(Fe) and diatomite for the photo-fenton degradation of phenol - Matskan, P. A. (Kinetics and catalysis)
Porous composites based on a MIL-100(Fe) metal–organic framework and a natural diatomite material have been synthesized. The composites are characterized by a specific surface area of 322 and 441 m2/g and a hierarchical pore structure represented by wide pores of the original diatomite and narrow meso- and micropores of the formed MIL-100(Fe) particles. The effect of synthesis approach on the structure of the composites and their catalytic properties in the photocatalytic degradation of phenol has been studied. In the composite synthesized with the preimpregnation of diatomite with an iron nitrate solution, MIL-100(Fe) particles are mostly formed inside the diatomite pores. The composite samples exhibit catalytic activity in the photo-Fenton degradation of phenol. The highest activity is exhibited by the sample synthesized without any preimpregnation of diatomite; this sample is characterized by the dominant formation of MIL-100(Fe) particles on the external surface of the diatomite.